Kinetics of graphite expansion during eutectic solidification of cast iron. (April 2014) - Alonso, G.; Stefanescu, D. M.; Suarez, R.; Loizaga, A.; Zarrabeitia, G.
<x content-type="archive" xml:space="preserve">Abstract</x> The paper introduces a new linear displacement analysis (LDA)/thermal analysis (TA) experimental device for measuring linear displacement during the solidification of cast iron. The experimental device comprises a sand mould encased in a steel shell that prevents mould wall movements. Thus, only the linear displacement caused by the shrinkage or expansion of the metal is recorded by the transducers. Two quartz rods introduced directly at different heights into the liquid metal and connected to two transducers record the linear displacement during the liquid–solid transformation and subsequent cooling. Two thermocouples positioned at the same height with the quartz rods allow for the concomitant TA and LDA and thus for the direct correlation between expansion/contraction and the temperature change during solidification events such as graphite formation. The LDA device was used to study the differences in the solidification mechanisms of irons with different graphite morphologies (lamellar, compacted/vermicular and spheroidal) at carbon equivalent in the range of 3·7–4·4%. The analysis included the LDA and TA curves and full metallographic characterisation of the cast irons. In general, graphite expansion increased as the graphite shape changed from lamellar, to compacted and then to spheroidal. The most important process variables are the magnesium and carbon contents. Higher Mg residual and C in the iron produced more graphite expansion. Compacted graphite (CG) iron was particularly sensitive to the Mg residual. Indeed, the high Mg CG irons exhibited similar graphite expansion to that of spheroidal graphite (SG) iron, while the low Mg CG iron expansion was closer to that of the lamellar graphite (LG) iron. Graphite expansion increased for all data with the time interval over which graphite expansion occurred. It also increased with both carbon and carbon equivalent. The time for graphite expansion increased noticeably with the carbon content of the iron. It did not depend on the graphite shape. By combining TA and LDA, it was possible to plot the evolution of graphite expansion as a function of the fraction solid and thus to understand the kinetics of graphite expansion. The amount of expansion available at the end of solidification was quantified. Such data, when correlated with process variables, will be useful in decreasing microshrinkage and in producing riserless compacted and SG irons.